Enter whining - Drescher, Fran 1957- (Regan Books, 1996)
Known and loved by millions around the world as the star of the top-rated CBS TV series The Nanny, Fran Drescher tells her hilarious life story and offers a fresh, funny, and irreverent backstage look at Hollywood and its stars.
Keywords: Drescher, Fran; Drescher, Fran -- 1957-; Actors -- United States -- Biography; Autobiografie; USA; Biografie